Music-assisted relaxation during transition to non-invasive ventilation in people with motor neuron disease. Issue 1 (1st June 2016) - Tamplin, Jeanette; Baker, Felicity; Bajo, Eleanor; Davies, Rebecca; Bolger, Karen; Sheers, Nicole; Berlowitz, David
Abstract : Background : Motor Neuron Disease (MND) is a progressive neurological disease causing muscle weakening and wastage, leading ultimately to respiratory failure. Non-Invasive Ventilation (NIV) is recommended to help patients manage respiratory insufficiency. Objective : To examine the feasibility and effectiveness of a Music-Assisted Relaxation (MAR) intervention on anxiety, quality of life, and NIV-use during the first 3 months of using NIV. Methods : Using a cohort mixed-methods design, data were collected at baseline, 7-days and 3-months for 18 participants who self-selected MAR or standard care. Measures included: Hospital Anxiety and Depression Scale, Assessment of Quality of Life–8D, and NIV-use data from participants' machines. Qualitative interviews were conducted with a subgroup of participants. Conclusions : MAR may be an useful intervention to promote relaxation, address anxiety, and distract from effects of NIV for patients commencing NIV use. MAR may have a role in alleviating the distress of NIV initiation.